Generation Z and Sustainable Consumption: An Analysis of Their Willingness to Pay for Green Product - Oktarini, Kurnia; Saputri, Ulfah Tika; Pratiwi, Clarissa Widya; Salamittasbihi, Da’iyah Fi; Pandiya, Ika Satya (Jurnal Sains Sosio Humaniora, 2025)
This study investigates the extent to which Generation Z consumers in Palembang are willing to pay a price premium for environmentally friendly products. Employing a quantitative correlational design, the study positions willingness to pay as the dependent variable, while environmental concern, green future estimation, perceived green benefits, and perceived green product quality serve as the independent variables. The research population comprises Generation Z consumers residing in Palembang, with 1,004 respondents selected using purposive sampling. Data were obtained through an online questionnaire containing 15 items assessed on a five-point Likert scale. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that environmental concern, green future estimation, perceived green benefits, and perceived green product quality each exert a positive and significant influence on consumers’ willingness to pay for green products. These results indicate that Generation Z in Palembang possesses a relatively strong environmental awareness and a considerable readiness to support sustainable consumption through their purchasing behavior. This study enriches the literature on green consumer behavior by emphasizing the importance of cognitive and perceptual factors in explaining willingness to pay among Generation Z consumers.